Comparison treatment of medium-sized volar fingertips defects with modified triangular neurovascular unilateral advancement flap versus digital artery dorsal perforator flap - Lixi Zhu; Feiya Zhou; Xian Zhang; Xue Zhang; Pinghu Jin (Journal of Orthopaedic Surgery and Research, 2024)
Abstract Purpose The reconstruction of medium-sized soft tissue defects of the fingertip remains a challenge for hand surgeons. The aim of this study was to compare the outcomes of modified triangular neurovascular unilateral advancement flap and digital artery dorsal perforator flap in the treatment of this injury. Methods From May 2018 to May 2022, 70 patients with medium-sized volar soft tissue defects were enrolled. The patients were divided into two groups based on the flap type: modified triangular neurovascular unilateral advancement flap (Group A) and digital artery dorsal perforator flap (Group B). The debridement times, defect size, operation time, and flap survival rate were recorded. At follow-up, hand function, aesthetics, and complications were evaluated. Function was evaluated using the TAM score. The aesthetics of the reconstructed and donor sites were assessed using the vancouver scar scale (VSS). The static two-point discrimination of the finger pulp served as a measure of tactile agnosia. Results A total of 10 patients were lost to follow-up for various reasons, resulting in 30 cases remaining in each group. The general information of the two groups showed no significant differences in age, sex, injury side, cause of injury, time from injury to surgery, and operation time (P > 0.05). Additionally, the debridement times and size of the defect were similar between the groups (P > 0.05). However, the operation time was significantly shorter in Group A compared to Group B (P = 0.001). With regard to complications, there was no significant difference between them. At one-month follow-up, TAM scores indicated that Group B performed significantly better than Group A. However, at the final follow-up period, there was no significant difference in TAM scores between the two groups. When considering the VSS, significant differences were observed between the two groups in both the reconstructed site and donor site. Conclusion Both flaps can effectively repair medium-sized fingertip defects. Furthermore, the modified triangular neurovascular unilateral advancement flap offers anatomical reconstruction possibilities, ensuring satisfactory sensation and cosmetic contour.